Givetian megaspore assemblages of the Mikhailovksy mine (Kursk oblast) - D. I. Marinina; O. A. Orlova (Известия высших учебных заведений: Геология и разведка)
Background. Disperse megaspores from the Givetian deposits of the Mikhailovsky mine, Kursk Oblast, were studied for the first time. Following chemical maceration of the samples, their selection and identification, 12 species belonging to 8 genera of disperse megaspores were identified. The conducted analysis of the layer-by-layer distribution of disperse megaspores in the studied outcrop, two megaspore assemblages were established, describing the lower (M1) and upper (M2) parts of the section. Both assemblages are dominated by small-sized azonate megaspores of the Hystricosporites McGregor genus, although belonging to different species. The upper assemblage (M2) is more diverse in terms of taxonomic composition. Along with the Givetian deposits of the Mikhailovsky mine, the identified disperse megaspores were previously found in coeval deposits of Canada and Libya.Aim. To study of disperse megaspores from the Givetian deposits of the Mikhailovsky mine (Kursk Oblast) and to establish megaspore assemblages for this section.Materials and methods. Samples of the clay deposits of the Givetian stage of the Middle Devonian from the Mikhailovsky mine (Kursk Oblast, Zheleznogorsk) were collected by employees of the Paleontological Institute of the Russian Academy of Sciences (PIN RAS) in the summer of 2017. The samples were macerated at the Department of Paleontology using concentrated (55%) hydrogen peroxide. The samples heavily contaminated with megaspores were additionally treated with hydrofluoric acid and further purified in hot drops of denaturated alcohol. Selection, counting, and determination of macerated samples of disperse megaspores were carried out using an Olympus CZ65 stereomicroscope at a 20x magnification or greater. Microphotographs were taken using a TESCAN Vega-3 scanning electron microscope (PIN RAS).Results. A total of 12 species belonging to 8 genera were identified. These included Hystricosporites McGregor, Verrucisporites Chi et Hills, Nikitinsporites Chaloner, Biharisporites Potonié, emend. Glasspool, Ancyrospora Richardson, Contagisporites Owens, Grandispora Hoffmeister, Staplin et Malloy, emend. McGregor, and Lagenicula (Bennie et Kidston) Dybova-Jachowicz et al. On the basis of disperse megaspore distribution along the section, two megaspore assemblages were established: M1 (lower, layers 7–12) and M2 (upper, layers 18–21).Conclusion. The disperse megaspores established in the Givetian deposits of the Mikhailovsky mine were early described in the Arctic Canada. The majority of the studied megaspores were most likely produced by lycopsids. This conclusion is based on their comparison with identical in-situ megaspores, as well as on the ultrathin structure of the sporoderm, previously established for some species. Consequently, the Givetian forests of the studied region were populated with numerous lycopsids, including tree-like ones, among heterosporous plants, with an insignificant role of archaeopteridalean tree-like species.